111 Improving the quality of echo surveillance in patients receiving trastuzumab chemotherapy. (17th July 2020) - Cassar, Mark Philip; Stirrup, James
Abstract : Background: With a large number of patients receiving cancer treatment at our Hospital, the echocardiography (ECHO) department runs frequent specialised transthoracic echocardiogram lists to monitor left ventricular (LV) function in patients receiving potentially cardiotoxic medication. A significant number of these are HER2 positive breast cancer patients receiving trastuzumab, which, based on several large studies, is associated with a 1.7 – 20% risk of LV dysfunction.1 This is usually reversible on withdrawal of trastuzumab and initiation of heart failure therapy. Since echocardiographic findings can impact decision making in these patients, the aim was to produce uniform echocardiogram reports that adhere to the latest guidance and provide an interpretation of the echocardiographic data acquired. Methods: The latest guidance on LV function surveillance was used to update the department protocol. Our first intervention (PDSA 1) consisted of the design of a flowchart to aid interpretation of echo findings; this was printed and placed in every echo room (Figure A ). Our second and final intervention (PDSA 2) consisted of the design of a desktop application to facilitate the calculations required (Figure B ). Data entry is restricted to just 4 cells: baseline and current EF baseline and current GLS Changes in EF and GLS are calculated automatically from this data and generate an automatic, guideline-based conclusion for insertion into the report conclusion. Conclusions can be generated from changes in EF alone, but none is generated from GLS values alone. The app is designed to reject impossible or extreme values (e.g. positive GLS values, EF >…) and prompts the user that an error has occurred. The effect of these interventions was assessed by auditing echo reports for a number of variables, such as whether LV function was being compared to the baseline echo and whether a conclusion aiding decision making reflective of the latest guidelines was included in the echo report. Results: On baseline review of 25 TTE reports of patients receiving trastuzumab (all having Simpson's BP calculated): 72% of studies had GLS calculated, but none compared this to the baseline echo None of the studies compared the EF to the baseline study None of the studies had a conclusion reflective of current guidelines Following each intervention, a further 25 echo reports were reviewed. Following the final intervention, of the 25 echo reports audited: All had a GLS calculated. 84% calculated the change in GLS compared to the baseline data. 88% calculated the change in EF compared to the baseline study 92% contained a conclusion that was in line with current guidelines. The project resulted in a statistically significant improvement in reports comparing GLS change and EF change with baseline values, together with reports including a relevant conclusion reflective of current guidelines (p<0.0001). Conclusions and Implications: The use of a flowchart and introduction of a desktop application has resulted in high quality standardised echo reports which are reflective of the latest guidance. Consistent high-quality echo reports in these patients will serve as an aid to decision making regarding continuation or cessation of potentially cardiotoxic chemotherapy. References: Seidman A, Hudis C, Pierri MK, et al . Cardiac dysfunction in the trastuzumab clinical trials experience. J Clin Oncol 2002;20 :1215–1221. Conflict of Interest: None